Analysis of Arabic Phonetic Articulation Point - Al-Mutairi, Salma Mohammed (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to analyze the differences between traditional and modern classifications of Arabic articulation points and their impact on pronunciation and language instruction. Using a descriptive-analytical approach, the study compares classical phonetic models such as Al-Khalil ibn Ahmad’s (8 points) and Sibawayh’s (16 points) with modern classifications like Kamal Bishr’s (11 points). Spectrographic tools, particularly Praat, were employed to evaluate precision in articulatory categorization. The findings suggest that modern classifications are approximately 25% more accurate in capturing articulatory nuances, enhancing pronunciation teaching and error correction. The study recommends incorporating phonetic analysis tools into Arabic language instruction, especially for non-native speakers.